Transition-metal single atoms embedded into defective BC3 as efficient electrocatalysts for oxygen evolution and reduction reactions. Issue 2 (7th January 2021) - Zhou, Yanan; Gao, Guoping; Chu, Wei; Wang, Lin-Wang
Abstract : The best catalyst for OER is Co@VB with η OER of 0.43 V followed by Ni@VC with η OER = 0.47 V. For the ORR process, the best catalyst is Rh@VB with η ORR of 0.40 V followed by Pd@VB and Pd@VC ( η ORR = 0.45 V). Abstract : Searching for high-activity, stable and low-cost catalysts toward oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are of significant importance to the development of renewable energy technologies. By using the computational screening method based on the density functional theory (DFT), we have systematically studied a wide range of transition metal (TM) atoms doped a defective BC3 monolayer (B atom vacancy VB and C atom vacancy VC ), denoted as TM@VB and TM@VC (TM = Mn, Fe, Co, Ni, Cu, Ru, Rh, Pd, Ir and Pt), as efficient single atom catalysts for OER and ORR. The calculated results show that all the considered TM atoms can tightly bind with the defective BC3 monolayers to prevent the atomically dispersed atoms from clustering. The interaction strength between intermediates (HO*, O* and HOO*) and catalyst govern the catalytic activities of OER and ORR, which has a direct correlation with the d-band center ( ε d ) of the TM active site that can be tuned by adjusting TM atoms with various d electron numbers. For TM@VB catalysts, it was found that the best catalyst for OER is Co@VB with an overpotential η OER of 0.43 V, followed by Rh@VB ( η OER = 0.49 V), while for ORR, Rh@VB exhibits the lowest overpotential η ORR of 0.40 V, followed by Pd@VB ( η ORR = 0.45 V). For TM@VC catalysts, the best catalyst for OER is Ni@VC ( η OER = 0.47 V), followed by Pt@VC ( η OER = 0.53 V), and for ORR, Pd@VC exhibits the highest activity with η ORR of 0.45 V. The results suggest that the high activity of the newly predicted well dispersed Rh@VB SAC is comparable to that of noble metal oxide benchmark catalysts for both OER and ORR. Importantly, Rh@VB may remain stable against dissolution at pH = 0 condition. The high energy barrier prevents the isolated Rh atom from clustering and ab initio molecule dynamic simulation (AIMD) result suggests that Rh@VB can remain stable under 300 K, indicating its kinetic stability. Our findings highlight a novel family of efficient and stable SAC based on carbon material, which offer a useful guideline to screen the metal active site for catalyst designation.